Help‐Seeking in the School Context: Understanding Chinese American Adolescents' Underutilization of School Health Services. (8th July 2013) - Anyon, Yolanda; Whitaker, Kelly; Shields, John P.; Franks, Heather
ABSTRACT: BACKGROUND: This article examines whether school contextual factors, such as referral practices and peer dynamics, contribute to Chinese American students' underrepresentation in school health programs. METHODS: Data from the 2007 Youth Risk Behavior Survey (N = 1, 744) as well as interviews and focus groups (N = 51) with Chinese American users and nonusers of high school health programs were analyzed to identify aspects of the help‐seeking process unique to Chinese American students. RESULTS: Chinese American students primarily defined the need for school health services as having personal problems, engaging in early sexual activity, or using drugs. For the most part, they did not recognize their own health or psychosocial concerns as falling in these categories. Teacher referrals and peer dynamics were also salient factors in students' decisions to seek help from school health programs. Relationships with providers in strengths‐based prevention programs improved their utilization of individual therapy and reproductive health services. CONCLUSIONS: To increase Chinese American students' access of needed services, the organizational systems and social contexts of school health programs (in addition to the practices of individual clinicians) must be responsive to the needs and preferences of these ethnic minority youth.